Esterification of free fatty acid from simulated waste cooking oil using ionic liquid as catalyst - Wan Nur Izzati, Riza (2014)
Ionic liquid is a catalyst which is homogeneous (liquid phase) catalyst. Ionic liquid has been recognize as a potential catalyst in esterification of free fatty acid from waste cooking oil which contain high amount of free fatty acid due to the triglyceride hydrolysis during frying due to its properties which is adjustable by adjusting its combination of cation and anion. It also recognize as a substitution of sulphuric acid in biodiesel synthesis.